The Position of Electronic Evidence in the Police Investigation Process Based on the Criminal Procedure Code and Law Number 1 of 2024 Concerning ITE - Welfriede Siregar; Ahmad Ansyari Siregar; Nimrot Siahaan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The development of information technology has brought significant changes to modern crime patterns, which are increasingly committed through electronic media and leave digital traces. This situation demands adjustments to the criminal evidence system, particularly regarding electronic evidence. The Criminal Procedure Code (KUHAP), as the main criminal procedure law in Indonesia, does not specifically regulate the existence of electronic evidence, thus creating a normative vacuum in investigative practice. However, Law Number 1 of 2024 concerning Electronic Information and Transactions (UU ITE) is present as a lex specialis regulation that fully legitimizes electronic information and/or electronic documents as valid legal evidence and has the same evidentiary force as written evidence. This article aims to analyze the position of electronic evidence in the police investigation process through a normative juridical approach by examining the Criminal Procedure Code, the UU ITE, and law enforcement practices in the field. The results of the study indicate that electronic evidence plays a strategic role in uncovering crimes, especially digital-based crimes. However, its implementation still faces technical obstacles, data validity, limited human resources, and differences in interpretation among law enforcement agencies. Therefore, it is necessary to harmonize regulations, increase the capacity of investigators, and strengthen digital forensic infrastructure so that the use of electronic evidence can be more effective and accountable in the criminal evidence process.